Antonius Diogenes, Die unglaublichen Dinge jenseits von Thule Edition, Übersetzung, Kommentar - Schmedt, Helena (Millennium-Studien / Millennium Studies, 2020)
The Wonders Beyond Thule by Antonius Diogenes uniquely combines a range of themes, including aspects of a love story, fantastic journeys, and Pythagorean philosophy. The author reassembles this work, which has only been preserved through papyrus fragments as well as later authors' accounts, into a new edition that offers detailed philological and interpretive commentary on all of the surviving descriptions and fragments.